New AI for new frontier of intelligent science and technology: from PAPAI++ to new enterprise ecology - WANG Fei-Yue (智能科学与技术学报)
A brief on the new development of artificial intelligence, agentic intelligence, autonomous intelligence and the new AI in 2024, is presented with an outline for three potential directions in 2025.